Balet Rusia À La Indonesia: Sebuah Akulturasi Dalam Tari Kabaret Baliano Karya Rusdy Rukmarata - Yunda Kenanga Valindyputri (Gelar : Jurnal Seni Budaya, 2021)
This study discusses about the Russian ballet which is acculturated with the Nusantara culture in Indonesia. This research uses acculturation theory by Readfiled, Linton, and Herskovits in The Cambridge Handbook of Acculturation Psychology (2006). The purpose of this study is to identify how acculturation occurs in Russian ballet with Indonesian traditional dances and what influences it. This study uses a qualitative method that uses the literature study method, and is supported by interview techniques. The results of this study identified that acculturation occurs in one of the many works that combine Russian ballet with Nusantara dance and that experience can also affect the acculturation results of the work.